2021
DOI: 10.1016/j.pedn.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience and Its Association with Psychosocial Adjustment of Children with Chronic Illness: A Latent Profile Analysis

Abstract: Purpose: The purpose of this study was to investigate the characteristics of family resilience in a sample of Chinese families with children diagnosed with chronic illness using Latent Profile Analysis (LPA). In particular, we examined the association of family resilience profiles with the psychosocial adjustment of children, and identified the socio-demographic correlates of these latent profiles. Design and methods: A cross-sectional study was conducted at comprehensive hospitals and children hospitals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
3
10
0
1
Order By: Relevance
“…Among various socio‐demographic variables, we found that the higher the per capita monthly income and education level were, the higher the WFRQ‐C score was. Similar to a recent study conducted in Chinese children with chronic illness, in addition to factors related to the type of chronic disease and time since diagnosis, the results showed that family resilience was related to family monthly income, medical insurance, and family employment status (Dong et al, 2021). Robust family research in western culture finds that socioeconomic factors, particularly income and education, strongly influence marital and family functioning and stability (Cherlin, 2010), because those with low education and income have fewer opportunities, less access to resources, and higher financial strains on the family (Roche et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Among various socio‐demographic variables, we found that the higher the per capita monthly income and education level were, the higher the WFRQ‐C score was. Similar to a recent study conducted in Chinese children with chronic illness, in addition to factors related to the type of chronic disease and time since diagnosis, the results showed that family resilience was related to family monthly income, medical insurance, and family employment status (Dong et al, 2021). Robust family research in western culture finds that socioeconomic factors, particularly income and education, strongly influence marital and family functioning and stability (Cherlin, 2010), because those with low education and income have fewer opportunities, less access to resources, and higher financial strains on the family (Roche et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Notably, there is currently a lack of study investigating the relationship between different profiles of psychological resilience and work fatigue among nurses. Previous studies have examined this relationship in other populations, such as children and adolescents (Dong et al, 2021; Janousch et al, 2022), but they do not adequately represent the characteristics of nurses. Therefore, this study may potentially fill this gap.…”
Section: Discussionmentioning
confidence: 99%
“…Auch das familiäre Umfeld hat einen signifikanten Einfluss auf die Einschätzung der HRQOL. Niedrige familiäre Resilienz 22 sowie Ängste und Depressionen vor allem der Mütter 23 sind mit einer schlechteren HRQOL der Patient*innen vergesellschaftet.…”
Section: Chronische Erkrankungen Als Stressfaktorunclassified